Fingerprint image enhancement and reconstruction using the orientation and phase reconstruction - Gupta, Rashmi; Khari, Manju; Gupta, Deepti; González-Crespo, Rubén (Information Sciences, 2020)
Fingerprints are the one of the most important means in the forensics as a means of identification of the criminals owning to the uniqueness and the distinct features in them. Fingerprint identification is considered as an important means for the identification of the people around the globe. Minutiae are the details present in the human fingerprints which are used as a means of identification and verification. Minutiae are the distinctive points which can be used for the effective reconstruction of the fingerprint image. However, there was a limitation that was considered. The minutiae points are completely not enough for reconstruction of the image. Many spurious minutiae are not included and the results for the latent fingerprints are not as accurate as they are for the normal data sets. In this paper, a novel technique has been proposed which considers the minutiae density and the orientation field direction for the reconstruction of the fingerprint. Two public domain databases Fingerprint verification competition 2002 (FVC2002) and fingerprint verification competition 2004 (FVC2004) have been used for the experimental results and to validate the suggested methods for the fingerprint reconstruction and enhancement.
Keywords: fingerprint identification; minutiae; orientation field; ridge frequency; fingerprint enhancement; fingerprint reconstruction; Scopus; JCR